A study of some physical and chemical properties of local bee honey (Journal of the College of Basic Education, 2022)
Physical and chemical properties where estimated for the three samples of local honey. (honey mountain, clover honey and eucalyptus), amounting to viscosity (38.49, 17.24, 17.24), respectively, either Mlebojz density (1.12, 1.14, 1.14) g/ml, respectively, and was a honey color ( bright yellow, light yellow, dark yellow), respectively, and the refractive index (499.1, 498.1, 497.1), respectively, either total soluble solids were (50.83, 1.83, 90.83), while the percentage of fructose (32.40%, 40.70%, 28.50%), respectively, either sugar glucose ratio was (38.26%, 36.70%, 38.30%) respectively, and the sum of fructose and glucose (70.66%, 77.40%, 66.80%) respectively, and the proportion of either sucrose (7.17%, 0.005%, 0.003%) respectively, and estimated the relative humidity was (15.5% , 0.0018%, 16.00%) respectively, as estimated total acidity were (0.0018, 0.0020, 16.12) Mlamkavye\ kg respectively, have been studied pH and the pH (3.91, 3.51, 3.92) respectively, and found that the amount of ash ( 0.19%, 0.17%, 0.18%) respectively, and values ​​ranged protein concentration (539.52, 294, 519.95) mcg/ mL respectively, while the proportion of proline (0.76, 0.30, 0.15) mg/kg respectively, as estimated effectiveness of the enzyme glucose Aoxdez as she was (0.008, 0.011, 0.000) mg H2O2/g/h respectively, and estimated the amount of hydroxy instance furfural in honey as it was (91.5, 38.40, 23.42) mg/kg respectively, as noted the presence of some metallic elements in honey samples consisted of magnesium and iron and copper , lead, and cadmium, cobalt , nickel and chrome , but the honey mountain vacate chrome. The results of the initial detection of the honey samples it contained three compounds effective secondary Almthmthelh Baltaninat and Alsabonyat Alclaicosadat and flavonoids and terpenes and phenols and coumarin.